Voudou van New Orleans naar Cotonou op het ritme van de goden. Leendert van der Valk. VBK België, Antwerpen, 2017 - Van Damme, Patrick (Afrika Focus, 2018)
This very, very interesting book was written by a Dutch modern music journalist who set up a crowdfunding campaign to be able to go and visit the roots of the voodoo music (and culture). His journey takes him and us to the USA (Mississippi and New Orleans’ mardi gras), the santeria in Cuba, Haiti, Surinam and nally, Togo and Benin. He participates in ceremonies, goes to con- certs and ‘events’, has many discussions, and brings a very well-documented impression of what voodoo is, and is not. The book leads us to numerous artists who have taken inspiration from the traditional drums and beats, and should thus be read with one’s vinyl or CD collection at hand, or else with youtube as universal reference for all things voodoo ! The work is very well-written in owing Dutch, draws on written references and offers a list of key words that will help the reader to understand the ner details of voodoo culture. Hopefully this book will be translated into Eng- lish so as to let a wider audience bene t from its many insights.